Trellis-coded (n,2)MPPM for indoor wireless infrared communication - Wei, Xue Fei. (2009)
In this thesis we propose a trellis-coded (n,2)MPPM (multiple pulse-position mod-ulation)technique and examine its performance on non-directed wireless infrared channel. More specifically, we use the technique to achieve high power efficiency under moderate bandwidth expansion rate. We match the coding scheme to ISI (intersymbol interference)channel to mitigate multipath power penalty.